Chemotherapeutic effect of Ficus carica latex on experimentally induced hamster buccal pouch carcinogenesis - Mohamed Alaa Al-Dosoki; Amr Saad Abd Al-Wahab; Amr Mahmoud Mohamed; Kamal Abd El-Rahman Kamal; Ahmed Abd-Alshakor Abd-Alhafez; Ashraf Yehia Shamia; Ahmed Hussein Gaber; Galal Abou Elyazied Nasr; Hany Mahmoud Mahmoud; Ahmed Samir Zakria; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
The presentresearch aimed to assess the chemotherapeutic effect ofFicus carica latex (fig latex)on experimentally induced hamster buccal pouch (HBP) carcinogenesis. Material and methods: Thirty five-week-old Syrian male hamsters weighing between 80 and 120 grams apiece were split up into three groups (n=10):Group I: left untreated, Group II: 7, 12-dimethyl benz[a]anthracene (DMBA) applied topically on three occasions a week for fourteen weeks at a concentration of 0.5% in liquid paraffin, Group III: DMBA (0.5% in liquid paraffin) was applied topically on three occasions a week for fourteen weeks, and 0.5 cc of fig latex had been administered intramuscularly every day for 4 weeks. Results: The present research findings demonstrated that fig latex had a positive regression impact on tumor growth. The occurrence of oral squamous cell cancer (OSCC) was considerably decreased by the fig latex, going from 100% to 50%. The immunohistochemical analysis displayed that the fig latex decreased the expression of the antiapoptic marker Bcl-2 with non-significant variationin comparison to GII (p value > 0.05). Conclusion: These results suggest that the latex of Ficus carica may offer a new chemotherapeutic medication since it inhibits proliferation and induces apoptosis in human oral cancer cells.